THE JUDICIAL INDIVIDUALIZATION OF THE PUNISHMENT. ALTERNATIVES TO DETENTION IN THE UNITED KINGDOOM CRIMINAL LAW - Andrei-Viorel IUGAN (Challenges of the Knowledge Society)
The simple fact that a person commits a crime doesn’t mean necessary that that person must be imprisoned. It’s for the court to decide which is the proper sanction that must be imposed to that person. The state must create a very organized system of alternatives to detention, and as a result of those alternatives detention should be the ultimate measure for the judge to pronounce. The legislation must regulate a wide variety of means of individualization, alternative to detention, and the courts must choose the one that assures the social reintegration of the delinquent and the restore of the public order. In this study we are going to present how are the alternatives to detention regulated in the UK’s crimal law system and what are the results of this system.